دراسة تحليلية نقدية لمفروشات الشارع شوارع مدينة اللاذقية مثالاً (Latakia University Journal -Engineering Sciences Series, 2016)
تلعب مفروشات الشارع Street furniture دورا مميزا في رسم صورة المحيط العمراني الذي تتواجد فيه، وذلك بإعطائه طابعاً معاصراً يواكب التطور الحضاري والاجتماعي، الغاية الاساسية لتلك المفروشات هي خدمة المستخدمين، وتواجدها الكثيف في الشارع، يجعل منه هدفاَ وغاية في الوقت نفسه، لذلك فإن تناسق عناصرها، وانسجامها مع محيطها، هو الاساس في اكتسابه قيمة جمالية ووظيفية هامه.ما نراه اليوم في شوارعنا، هو الاهمال المتزايد لهذا الفضاء الاجتماعي الهام، وذلك من خلال اهمال مكوناته الاساسية، واختزال وظيفته في مجال ضيق؛ فمن مكان للقاء والتواصل والحركة الى طريق للعبور، أهم مظاهر الاهمال تتمثل في طريقة التعاطي مع تلك العناصر من حيث التصميم الى التنفيذ فالتركيب والصيانة، ومن المعروف ان اي خلل او تقصير في اي منها يخرج تلك المفروشات من الخدمة، ويحولها الى عائق في الطريق عوضا من ان تكون عنصراً يغني المكان ويخدم المارة. Street Furniture plays a significant role in shaping the urban environment to which it belongs by giving it a contemporary line that matches the cultural and social development, wherein the final aim is to serve the users. The overwhelming presence of these devices in the streets makes it a target and a goal at the same time. So the harmony and consistency of these elements with the environment and its surroundings is the basis of the acquisition of aesthetic and functional important value.What we see today in our streets is the growing neglect of this important social space, through the neglect of basic components, and narrowing down its function by transferring it from a meeting place for communication and movement to something to pass by. The most important manifestations of neglect is the way to deal with these items in terms of design, manufacturing and maintenance. It is known that any defect or failure in any of these items means making it out of service, and turning it into an obstacle in the street rather than an element whitch nourishes the place and serves the pedestrians.